Association of rs7260002 of chorionic gonadotrophin β5 with idiopathic recurrent spontaneous abortion in Chinese population - Sun, Yong; Ji, Xuan (Journal of assisted reproduction and genetics, 2014)
Purpose Low levels of serum hCG during the first trimester is regarded as a predictor of miscarriage. This study was designed to examine whether variance in chorionic gonadotrophin β5 ( Cgb5 ) gene confers risk to recurrent spontaneous abortions (RSA) in Chinese women. Methods We recruited a total of 454 RSA subjects and 460 controls from our medical center between the years 2010 to 2013. rs7260002, which resides in the promoter region of Cgb5 , was genotyped through direct sequencing. Results The carriers with the minor allele of rs7260002 had reduced risk of RSA ( P = 0.018; P adjusted = 0.032; OR: 0.76; 95 % CI: 0.61–0.96). Genotype frequency was further analyzed under additive, recessive, and dominant models. Significant differences between the RSA subjects and controls were detected under additive and recessive models (P additive = 0.040; P recessive = 0.010). Conclusions The current study identified a protective allele of the Cgb5 gene against RSA. Functional studies are required to elucidate the effect of the identified SNP on CGB expression and HCG hormone activity.